Current challenges, threats and risks to national security as an object of NABU's activities - Suhovetzkyj, Serhii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The defining form of providing the national security of Ukraine is and should be a well-thought-out and balanced state policy in accordance with the requirements of legislation, current regulatory acts, adopted national doctrines, strategies and programs in the appropriate areas of activity. At the same time, the specification of forms and methods, means and resources for providing national security at each stage can change adequately to the level of threats to national interests. However, a comprehensive systematic approach to taking into account and analysing factors that affect the violation of national interests and, accordingly, the level of national security should remain an invariable requirement under all conditions. This directly concerns the practice of special competence bodies. Exceptional attention should be paid to the formation of preventive measures that should be focused on existing and potential challenges, threats and risks. The leading role here is played by the National Anti-Corruption Bureau of Ukraine (NABU).Based on the results of the research, a number of scientific results were obtained, including attention was drawn to the problems of challenges, threats and risks to national security and national interests of Ukraine in the modern conditions of a globalized world. Based on the study of the theoretical and methodological foundations of the administrative and legal mechanism for providing national security of Ukraine, there are formulated the features of the approach to the correct orientation of authorized state structures and institutions in the development and implementation of specific measures and actions to prevent, avoid or minimize negative results from certain challenges, threats and risks to national security. The classification of threats, challenges and risks to national security, the prevention of which may relate to the objects of activity of the National Anti-Corruption Bureau of Ukraine (NABU), is systematized. There are formulated conclusions in terms of responding to current challenges, threats and risks with an effective administrative and legal mechanism, appropriate information support, analytical forecast estimates for the development of proposals to reduce the level of risks and threats to national security.